EVALUATION PROGRAM FOR INCREASING VALUE ADDED AND COMPETITIVENESS OF HORTICULTURAL PRODUCTS IN SUPPORTING SUSTAINABLE AGRICULTURE (EVALUATION RESEARCH ON THE MULYATANI GAPOKTAN IN BREBES) - Fajar Anggraeni; Rosadi Rosadi; Rita Retnowati (Journal of Science Innovare, 2021)
The purpose of this study is to evaluate the implementation of the program to increase the added value and competitiveness of horticulture through APBN funds that have been implemented by the Directorate of Processing and Marketing of Horticultural Products at the Mulyatani Gapoktan in Brebes Regency. This program is expected to support sustainable agriculture in Brebes district. The government strongly supports the development of shallot cultivation in Brebes district, which is the largest center for shallot commodities in Central Java. Increased added value can be obtained by farmers at the time of starting cultivation, post-harvest to marketing. By doing good and correct cultivation, it can increase the productivity produced (18 tons/hectare). The use of organic materials and reducing the use of chemical pesticides in onion cultivation is a form of added value obtained by farmers because the production costs for purchasing chemical pesticides reach 8% of the costs incurred. then if done postharvest properly and correctly it can reduce losses (damage) that occur so that the product has a high selling value. The added value of shallots obtained by Gapoktan Mulyatani is apart from the cultivation and postharvest processes, as well as in the marketing process of fresh and processed forms (fried onions, crispy onions, and onion paste), so that the shallot business can support sustainable agriculture because of the shallot business process. starting from upstream to downstream. The purpose of providing postharvest infrastructure assistance and shallot processing facilities at the Mulyatani Gapoktan in Brebes Regency by the Directorate of Horticultural Product Processing and Marketing is to implement a program to increase added value and horticultural competitiveness to improve the welfare of members of the shallot farmer group. So that the results of this evaluation will be used as a reference that this program can still be continued by involving other agencies so that the program runs according to the targets to be achieved.